European Union Timber Regulation: is it legal? - Fishman, A.; Obidzinski, K. (Wiley, 2014)
The recent entry into force of the European Union (EU) Timber Regulation completes the EU's anti‐illegal logging policy framework – the most comprehensive legislative effort to combat illegal logging in the world. The Regulation prohibits the import of timber to the European market that violates applicable laws of the harvest country, and requires that importers conduct due diligence to mitigate the risk that their inventories contain illegal timber. Despite this strong stance, the Regulation's ability to reduce the incidence of timber illegality depends on its ability to withstand challenges under international trade law. No case yet decided by the World Trade Organization's dispute bodies has considered the implications of trade restrictions built on foreign definitions of legality. An analysis of the General Agreement on Tariffs and Trade and of relevant trade and environment cases reveals a possibility that the EU Timber Regulation may constitute an illegal trade barrier.